DESIGN AND OPTIMIZATION OF ROTARY ROBOT ACTUATORS FOR HIGH-PRECISION CARTRIDGE CAP ASSEMBLY APPLICATIONS IN THE MANUFACTURING INDUSTRY - Veri Fernando; Desmarita Leni; Muchlisinalahuddin Muchlisinalahuddin; Yassirli Amri (International Journal of Multidisciplinary Research and Literature, 2026)
The use of Rotary Actuators in Industrial Automation systems requires adequate mechanical protection to ensure product quality, system reliability, as well as component durability and safe operation. However, many of the existing machine designs and assembly processes do not fully take into account structural strength, precision quality, ease of adjustment, and maintenance efficiency. This study aims to develop and design the assembly process of high-quality cartridge covers along with their installation system for rotary robotic actuators, taking into account aspects of quality, safety, functionality, and practical implementation. The research methodology includes a literature review, cause analysis, testing, and evaluation. Testing was conducted based on defect rate and the accuracy and precision of the system. The evaluation results showed a significant performance improvement after replacing the pneumatic actuator systems with electric actuators and making mechanical design improvements. Repeatability increased by about 87.6%, the defect rate measured by DPPM decreased by about 92%, and the safety factor reached 2.4, indicating a strong mechanical safety margin. In addition, the operation cycle time remains stable, supporting production needs without compromising reliability. The decrease in DPPM itself is a manufacturing quality metric that measures the number of defective units per one million productions, commonly used to assess the quality and reliability of the production line. These findings confirm that the cartridge cover assembly and installation design developed provides better mechanical protection, facilitates installation, and reduces product defects. Thus, the rotary electric actuator is superior in reducing DPPM and the level of precision.